A Newborn with Cleft Palate Associated with PTEN Hamartoma Tumor Syndrome - Ulf Nestler; Daniel Gräfe; Vincent Strehlow; Robin-Tobias Jauss; Andreas Merkenschlager; Annika Schönfeld; Florian Wilhelmy (Clinics and Practice)
Background: PTEN hamartoma tumor syndrome (PHTS) has evolved into an umbrella term for a range of syndromes, characterized by loss-of-function variants in the phosphatase and tensin homolog (PTEN) tumor suppressor gene on chromosome 10q23.31. This can result in a lifelong tumor predisposition in patients. Often, the syndrome is diagnosed in early childhood because of macrocephaly, dermatological findings, or development delay. Since the correlation between phenotype and genotype is weak, and the penetrance is age-dependent, this poses the question of the appropriate timing of potentially invasive and burdensome examinations for early cancer detection. Case: The present report describes an infant with cleft palate associated with PHTS, a rare occurrence, though the initial report of Cowden syndrome already pointed to oromaxillofacial abnormalities. The recent pediatric literature is reviewed to assess which clinical symptoms should raise suspicion of PHTS and may then lead to early genetic counseling. Conclusion: Since the amount of prospective data remains limited, and the estimation of tumor risk during infancy and adulthood is very difficult, we advocate for early and broad genetic testing in suspected cases, to gain more insights into this rare disease and allow for better counseling for patients and their families.